2016
DOI: 10.1111/ppe.12278
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Gestational Diabetes: Effect of Smoking Status during Pregnancy

Abstract: Background-Vitamin D status, as measured by serum 25-hydroxyvitamin D (25(OH)D), has been shown in some studies to be inversely associated with gestational diabetes risk. Recently, it has been suggested that maternal smoking status may modify this relationship. We explored the association between 25(OH)D concentration and gestational diabetes and determined if there was an interaction between smoking and 25(OH)D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In our study, we detected no difference in 25(OH)D levels between smokers and non‐smokers. However, similar interactions have been described between maternal 25(OH)D status and gestational diabetes . The authors of these studies postulated a role for the antiinflammatory and antioxidant effects of vitamin D that might mediate the association between 25(OH)D and gestational diabetes.…”
Section: Discussionmentioning
confidence: 67%
“…In our study, we detected no difference in 25(OH)D levels between smokers and non‐smokers. However, similar interactions have been described between maternal 25(OH)D status and gestational diabetes . The authors of these studies postulated a role for the antiinflammatory and antioxidant effects of vitamin D that might mediate the association between 25(OH)D and gestational diabetes.…”
Section: Discussionmentioning
confidence: 67%
“…Meanwhile, population‐based studies were implemented, but the results were inconsistent. Several prospective observational studies concluded that a low blood vitamin D level in the first and second trimesters could increase the risk of GDM, whereas others failed to find such associations . Besides, most randomised controlled trials (RCTs) supported the idea that supplementing with vitamin D during pregnancy could reduce the level of blood sugar and insulin, whereas the results of other related biomarkers were far from consistent and valid …”
Section: Introductionmentioning
confidence: 99%
“…Logistic regression models were adjusted for age, ethnicity, family history of diabetes, and prepregnancy BMI, and smoking during pregnancy, all known risk factors for GDM [19,40]. An additional model was calculated including gestational age, as GDM offspring had a significantly reduced gestational age and it is know that gestational age is a contributing factor to the fetal and maternal metabolome [41,42].…”
Section: Logistic Regressionmentioning
confidence: 99%